2018
DOI: 10.1111/bjet.12673
|View full text |Cite
|
Sign up to set email alerts
|

Community detection with opinion leaders’ identification for promoting collaborative problem‐based learning performance

Abstract: In the 21st century when knowledge‐based economy is emphasized, the cultivation of autonomous learning and problem‐solving abilities presents the importance. With web‐based collaborative problem‐based learning (CPBL), learners could more conveniently cultivate their problem‐solving abilities through autonomous learning. Nevertheless, learners are often guided to solve a target problem by the information announced by teachers during the CPBL processes. Individual learners often could not effectively absorb such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Students also thought the social group awareness was valuable for their collaboration by aiding them to identify the opinion leader or those they had less communication with. A previous study has revealed that identifying the opinion leader is important for collaboration because they play a crucial role to convey message for solving web‐based collaborative mission and significantly enhance group performance and group cohesion (Cheng & You, 2019). Additionally, being aware of those they had less communication, students could pay more attention to those members' postings and thus, more discussion or group interactions occurred.…”
Section: Discussionmentioning
confidence: 99%
“…Students also thought the social group awareness was valuable for their collaboration by aiding them to identify the opinion leader or those they had less communication with. A previous study has revealed that identifying the opinion leader is important for collaboration because they play a crucial role to convey message for solving web‐based collaborative mission and significantly enhance group performance and group cohesion (Cheng & You, 2019). Additionally, being aware of those they had less communication, students could pay more attention to those members' postings and thus, more discussion or group interactions occurred.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of this research have shown that the collaborative learning technique does influence mass collaboration. It has also been stated in the study of Chen and You (2019) that evaluation of the learner's performance has a significant effect on mass collaboration.…”
Section: Discussionmentioning
confidence: 97%
“…It is due to the reason that company can determine the effectiveness of mass collaboration in terms of enhancing the performance of employees. It has also been stated in the study of Chen and You (2019) that evaluation of the learner's performance has a significant effect on mass collaboration. In this manner, the H4 of the study has been developed to test the effect of evaluation of the learner's performance effect on the mass collaboration in retail companies of Jordan:…”
Section: Literature Reviewmentioning
confidence: 97%
“…The capacity of self-starting, being proactive, and having a persisting attitude to pursue a challenge or solve a problem. Chen and You [36] Coaching…”
Section: Time Managementmentioning
confidence: 99%